2017
DOI: 10.1089/ees.2016.0110
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Microbial Fuel Cells by Lactic Acid Bacteria and Anode Modification

Abstract: Indium Tin Oxide (ITO) conductive glass was modified by layer-by-layer modification of chitosan (CS) and aFe 2 O 3 nanoparticles. Lactic acid bacteria were the source of electrons in the studied microbial fuel cells (MFCs) system. When ITO/(CS/a-Fe 2 O 3 ) 4 /CS was the anode, external resistance was 626.6 O, while maximum current and maximum power density were 1.16 mA and 0.122 W/m 2 , respectively. These values were far higher than already reported results. Atomic force microscope image proved that ITO/(CS/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…7 To study this critical step involving the anode, the microorganisms located their, and their mechanism of electron deposition, it is necessary to choose proper anodic materials. 8 At present, more and more choices have got to fabricate or modify the electrode of MFCs, with nanomaterials, nanocomposites, graphene sheet and graphene oxides owing to their high surface area, porosity and prompt electron conduction properties. [9][10][11][12][13] The results showed that the electrodes fabricated or modied by nonamaterials exhibited excellent electrochemical activity.…”
Section: 4-6mentioning
confidence: 99%
See 1 more Smart Citation
“…7 To study this critical step involving the anode, the microorganisms located their, and their mechanism of electron deposition, it is necessary to choose proper anodic materials. 8 At present, more and more choices have got to fabricate or modify the electrode of MFCs, with nanomaterials, nanocomposites, graphene sheet and graphene oxides owing to their high surface area, porosity and prompt electron conduction properties. [9][10][11][12][13] The results showed that the electrodes fabricated or modied by nonamaterials exhibited excellent electrochemical activity.…”
Section: 4-6mentioning
confidence: 99%
“… 7 To study this critical step involving the anode, the microorganisms located their, and their mechanism of electron deposition, it is necessary to choose proper anodic materials. 8 …”
mentioning
confidence: 99%
“…The maximum power density values of ITO blank, ITO/(CS/α-Fe 2 O 3 ) 4 /CS and ITO/(CS/α-Fe 2 O 3 ) 8 /CS were 0.035, 0.124 and 0.084W/m 2 , respectively. The higher roughness of ITO/(CS/α-Fe 2 O 3 ) 4 /CS resulted in higher specific surface area available for growth of bacteria [160]. Following the trend, further development of MFC engaging LAB can be expected.…”
Section: Food Additivesmentioning
confidence: 89%
“…[180] Besides carbon cloth, indium tin oxide (ITO) electrode modified with Fe 2 O 3 nanoparticles possessed a rougher surface for a stronger adhesion of microbes and enjoyed an induced assembly of lactic acid bacteria on the conductive network. [181] Also, the hydrophobic carbon surface can be hydrophilized by coating Fe 2 O 3 due to the hydrogen bond formed between oxygen of Fe 2 O 3 and water molecules. [182] Moreover, the positively charged Fe 2 O 3 could be coated on graphene which is negatively charged, in order to overcome the electrostatic repulsion with the microorganisms, leading to a higher attachment of bacteria and a more uniform biofilm formation.…”
Section: Fe-based Carbon Compositesmentioning
confidence: 99%